PEDAGOGICAL BASIS OF IMPROVING DIGITAL LITERACY OF PHYSICAL EDUCATION TEACHERS IN HIGHER EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the pedagogical foundations for improving the digital literacy of physical education teachers in higher education. Digital literacy is interpreted not merely as the ability to use computers or technical devices, but as a professional pedagogical competence that includes the purposeful selection of digital resources, instructional design, monitoring of students’ physical activity, data-informed assessment, responsible use of artificial intelligence, and adherence to academic and ethical standards. The article reveals the relationship between digital transformation, the content of physical education, teacher professional competence, individualized monitoring of students’ motor activity, and the improvement of educational quality. It also substantiates diagnostic, methodological, motivational, technological, reflective, and institutional mechanisms for developing the digital literacy of physical education teachers.